Electroacupuncture of Baihui and Shenting ameliorates cognitive deficits via Pten/Akt pathway in a rat cerebral ischemia injury model - Su, Kaiqi; Hao, Wenxue; Lv, Zhuan; Wu, Mingli; Li, Jieying; Hu, Yanchao; Zhang, Zhenhua; Gao, Jing; Feng, Xiaodong (Frontiers in Neurology, 2022)
Cerebral ischemic stroke is a huge threat to the health and life of many people. Electroacupuncture (EA) at Baihui (GV20) and Shenting (GV24) acupoints can notably alleviate cerebral ischemia/reperfusion injury (CIRI). However, the molecular basis underlying the effectiveness of EA at the GV20 and GV24 acupoints for CIRI remains largely unknown. Our present study demonstrated that EA treatment at the GV20 and GV24 acupoints markedly alleviated middle cerebral artery occlusion/reperfusion (MCAO/R)-induced cognitive deficits and cerebral infarction in rats. Proteomics analysis revealed that 195 and 218 proteins were dysregulated in rat hippocampal tissues in the MCAO/R vs. sham group and thhhe EA vs. MCAO/R group, respectively. Moreover, 62 proteins with converse alteration trends in MCAO/R vs. sham and EA vs. MCAO/R groups were identified. These proteins might be implicated in the EA-mediated protective effect against MCAO/R-induced cerebral injury. GO enrichment analysis showed that 39 dysregulated proteins in the MCAO/R vs. sham group and 40 dysregulated proteins in the EA vs. MCAO/R group were related to brain and nerve development. Protein–protein interaction analysis of the abovementioned dysregulated proteins associated with brain and nerve development suggested that Pten/Akt pathway-related proteins might play major roles in regulating EA-mediated protective effects against MCAO/R-induced brain and nerve injury. Western blot assays demonstrated that Pak4, Akt3, and Efnb2 were expressed at low levels in the MCAO/R group vs. the sham group but at high levels in the EA group vs. the MCAO/R group. In conclusion, multiple proteins related to the protective effect of EA at the GV20 and GV24 acupoints against CIRI were identified in our study.